2018
DOI: 10.1111/bdi.12710
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic basis of psychosis in bipolar disorder: A positron emission tomography study

Abstract: Objectives Psychotic symptoms are a common feature in bipolar disorder (BD), especially during manic phases, and are associated with a more severe course of illness. However, not all bipolar subjects experience psychosis during the course of their illness, and this difference often guides assessment and pharmacological treatment. The aim of the present study is to elucidate, for the first time, the FDG uptake dysfunctions associated with psychosis in BD patients with and without a history of past psychotic sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 50 publications
1
0
0
2
Order By: Relevance
“…This is particularly relevant, given the evidence in favour of an imbalanced cAMP and calcium signalling and glycogen synthesis, with a potential impact on lactate metabolism and the overall cortical activity [99][100][101] . Clinical imaging studies have shown that glucose metabolism is altered in BD 102,103 and our study, in accordance with literature, underlines the contribution of microglia and astrocytes in this process 104,105 . It is important to note that 5 of the patients in our cohort where diabetic, although they were equally distributed between the samples (n = 2 in BD, n= 3 in CT) so the downregulation of insulin pathway genes is therefore probably not the result of this comorbidity.…”
Section: Discussionsupporting
confidence: 92%
“…This is particularly relevant, given the evidence in favour of an imbalanced cAMP and calcium signalling and glycogen synthesis, with a potential impact on lactate metabolism and the overall cortical activity [99][100][101] . Clinical imaging studies have shown that glucose metabolism is altered in BD 102,103 and our study, in accordance with literature, underlines the contribution of microglia and astrocytes in this process 104,105 . It is important to note that 5 of the patients in our cohort where diabetic, although they were equally distributed between the samples (n = 2 in BD, n= 3 in CT) so the downregulation of insulin pathway genes is therefore probably not the result of this comorbidity.…”
Section: Discussionsupporting
confidence: 92%
“…Por su parte un meta análisis también de ENIGMA (Enhancing Neuroimaging Genetics through Meta-Analysis), que evaluó estructuras corticales en adultos con TAB, identifico que estos, presentaban adelgazamiento en regiones parietales y temporales inferiores, incluidos los giros fusiforme y temporal medial los cuales están relacionados con el procesamiento y la conciencia visoespacial (40). Este hallazgo se correlacionó a su vez con disminución de metabolismo del giro fusiforme derecho en pacientes con TAB-I y antecedente de síntomas psicóticos, proponiendo que alteraciones en esta estructura , podrían considerarse biomarcador de psicosis en pacientes con TAB (41). Esto parece afín a los resultados de nuestro estudio en el que las alteraciones del giro fusiforme derecho fueron significativas en el subgrupo de PPM, el cual a su vez es el que presenta el mayor porcentaje de antecedente de síntomas psicóticos durante el curso del trastorno.…”
Section: Discussionunclassified
“…A tomografia por Emissão de Pósitrons (PETsigla em inglês), é outra técnica de imageamento cerebral funcional baseado na detecção de alterações no metabolismo neuronal, no entanto difere da fMRI pelo fato de empregar radiação ionizante como método contrastante, o que limita seu uso, devido ao custo elevado e ao potencial risco ao qual o indivíduo é exposto (Karrer et al, 2019). Além disso, assim como a fMRI, possui boa resolução espacial e baixa resolução temporal (Marotta et al, 2019).…”
Section: Tomografia Por Emissão De Pósitronsunclassified